THE SHIFT IN BLADELET PRODUCTION TRAJECTORY FROM LATE PALEOLITHIC TO NEOLITHIC: THE CASE STUDY OF IZEH, KHUZESTAN, IRAN. (February 2015) - Jayez, Mozhgan
Abstract : Chipped stone manufacturing organization is one of the most significant aspects of research on the lithic assemblages. This is a reductive process of manufacture through which raw material is reduced and transported through multiple stations. These stations can be traced based on the residues left at each of them. Such investigations are significant to explaining inter-assemblage variation through what is called the "reduction sequence." In this article, the author presents research on Late Paleolithic and Neolithic chipped stone assemblages from the Izeh Plain, southwest of Iran, regarding the nature of reduction sequences. This was an investigation of the determining factors in terms of lithic artifact manufacturing organization, including raw material availability, settlement patterns, and production trajectory of the lithic assemblages of sites in the region. While there is no difference observed in the junctures of bladelet production trajectory through the Late Paleolithic, a distinction of junctures is evident in bladelet manufacturing workshops in the Neolithic period.